Medical marketplace, commercialism, and Chinese medicine in the cholera pandemic in southeast coast China, 1961–1965 - Fang, Xiaoping (Palgrave Macmillan, 2021)
This paper aims to explore how local Chinese government regulated the medical marketplace, disciplined medical commercialism, and facilitated medical institutionalization of Chinese medicine in response to the global cholera pandemic that affected southeast coastal areas of China in 1962. It argues that the top-down state medical system, which was gradually established after 1949, started managing the previously unregulated medical markets as a part of the institutionalization process of Chinese medicine, particularly in rural areas. However, the retrenchment of the medical system after the Great Leap Forward not only aggravated the problem of scarcity in the medical marketplace, but also sabotaged participation in epidemic prevention, identification of suspect patients, and the reporting of epidemic information. Eventually, through regionalized regulation, downward extension of the medical system to villages, and further institutionalization of medical units, the government cracked down on commercialism among Chinese medical practitioners and facilitated the progress of epidemic prevention.